The Constitutional Court’s Judicial Activism in Indonesia: Constitutional Boundaries and a Progressive Legal Perspective - Tegar Maisa Julian; Qurrotul Uyun (Rule of Law Studies Journal, 2026)
Background:The Constitutional Court plays a strategic role in Indonesia's constitutional system as the guardian of the constitution, authorized to review laws against the 1945 Constitution. In practice, several Constitutional Court decisions demonstrate a tendency toward judicial activism, where judges not only interpret legal norms but also expand or create new ones. This phenomenon has given rise to debate regarding the limits of the Constitutional Court's authority within the framework of the separation of powers and its implications for the development of national law. Aims:This study aims to analyze the role of the Constitutional Court in implementing judicial activism and assess the effectiveness of this practice from a progressive legal perspective. Methods:This study uses a normative legal research approach with a statute approach, a case approach, and a conceptual approach. The research data was obtained through a literature review, which included primary legal materials in the form of legislation and Constitutional Court decisions, as well as secondary legal materials in the form of books, scientific journals, and academic literature. Data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing. Result:The research findings indicate that the Constitutional Court has implemented judicial activism in several of its decisions, reflected in decisions that are corrective, protective, and adaptive to social dynamics. This practice is evident in several important decisions that broaden the interpretation of legal norms to protect citizens' constitutional rights and fill legal gaps in the legal system. Conclusion:From a progressive legal perspective, the practice of judicial activism can be understood as the Constitutional Court's effort to achieve substantive justice in the Indonesian legal system. However, the implementation of this practice must adhere to the principle of separation of powers to avoid shifting authority between the judiciary and the legislature in a constitutional democratic system.